2005
DOI: 10.1016/s0140-6736(05)67423-5
|View full text |Cite
|
Sign up to set email alerts
|

Presbycusis

Abstract: The inevitable deterioration in hearing ability that occurs with age--presbycusis--is a multifactorial process that can vary in severity from mild to substantial. Left untreated, presbycusis of a moderate or greater degree affects communication and can contribute to isolation, depression, and, possibly, dementia. These psychological effects are largely reversible with rehabilitative treatment. Comprehensive rehabilitation is widely available but underused because, in part, of social attitudes that undervalue h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
919
0
54

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,077 publications
(988 citation statements)
references
References 45 publications
15
919
0
54
Order By: Relevance
“…Given the biological variability of ARHL, it may be difficult to devise a universal approach for improving ARHL. Rehabilitation strategies may also have to consider the contribution of peripheral and central auditory aspects [42, 45]. Testing these components selectively is not well established and no experience with screening for them exists.…”
Section: Discussionmentioning
confidence: 99%
“…Given the biological variability of ARHL, it may be difficult to devise a universal approach for improving ARHL. Rehabilitation strategies may also have to consider the contribution of peripheral and central auditory aspects [42, 45]. Testing these components selectively is not well established and no experience with screening for them exists.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing the ARHL-NIHL interaction in humans is difficult and the results of studies on hearing losses in noise-exposed and/or ageing ears are contradictory and highly variable [22][23][24][25]. This variability may arise from underlying differences in actual noise exposure and because, in part, noise and ageing are both under the influence of other intrinsic and environmental variables that can, by themselves, lead to HL or alter NIHL and/or ARHL vulnerability.…”
Section: Ageing and Hearing Loss 191mentioning
confidence: 99%
“…However, it remains difficult to distinguish dysfunctions of the auditory nerve caused by a decreased EP from those resulting from degeneration of spiral ganglion neurons [27]. Agerelated asynchronous activity of the auditory nerve could account for age-related declines in temporal resolving abilities, which are sometimes interpreted as solely caused by age-related changes in the properties of the auditory central nervous system [25]. Strial presbycusis is generally considered to be an ageing effect independent of exogenous damage, whereas ageing and insults accumulated (most commonly noise exposure) over the course of a lifetime are believed to be the key factors implicated in sensory presbycusis.…”
Section: Ageing and Hearing Loss 191mentioning
confidence: 99%
See 1 more Smart Citation
“…Age of onset, progression, and severity of age-related hearing impairment (ARHI) show great variation in the population, but with a demonstrable increased prevalence in males. 1 Heritability studies have shown that the sources of this variance are both genetic and environmental, with approximately half of the variance attributable to hereditary factors. 2 Only a limited number of genome-wide association studies (GWASs) have been performed up to now.…”
Section: Introductionmentioning
confidence: 99%